134 MATERNAL AND CHILD THROMBOPHILIA IN NEONATAL STROKE. (1st January 2005) - Curry, C. J.; Bhullar, S.; Holmes, J.; Hutchison, H. T.
Abstract : Several studies have implicated inherited and acquired thrombophilia as etiologically important in neonatal stroke (NS). In few have both mothers and children been tested, and MTHFR C677T and A1298C have not been evaluated in a large group. Between 1997 and 2004 we studied 50 infants and children with NS, excluding those with "watershed" infarcts or global ischemic injury. When possible, we tested both mother and child for the DNA mutations Leiden Factor V, Prothrombin 20210, and MTHFR C677T and A1298C; for protein C, S and Antithrombin III activity levels, and more recently for homocysteine and lipoprotein (a) levels. In mothers we obtained anticardiolipin antibodies (ACL), lupus anticoagulant and Beta 2 glycoprotein antibodies. Prothrombotic factors were identified in 34/50(68%) of all cases; in mother, child or both. More than one factor was present in 14/34(41%), and 3 mothers had 3 factors each. Leiden V was found in 5/40 (12.5%) of mothers and 4/48 (8%) of children; in only one instance was there concordance. Prothrombin 20210 was found in 5/47(11%) of children and only one mother. MTHFR homozygosity forC677T was found in 5/48 (10%) of children and 8/38 (21%) of mothers; compound heterozygosity for 677/1298 and homozygosity for A1298C were seen in 3 children each and 2 mothers each. In combination, 11/48 (23%) of children and 12/38 (32%) of mothers had homozygosity or compound heterozygosity for a MTHFR allele. MTHFR homozygosity was the sole prothrombotic factor identified in 5 cases, 2 of which were A1298C. Of interest, 20/48 (41%) of children were heterozygous for C677T as were 15/38 (39%) of mothers. Protein S deficiency was documented in 8 mothers and 1 child, whose mother was also deficient. Protein C deficiency was diagnosed in 2 children. Lipoprotein (a) levels ≥30 were found in 2/4 tested children and 3 tested mothers. Our observations confirm the high frequency of thrombophilia in NS as well as the frequent co-occurrence of more than one factor. Analysis suggests that mother and child may contribute independently to stroke risk as they are most often discordant for thrombophilic risk factors. MTHFR is common in our population but preliminary data suggests an increased frequency in Caucasians in this group as well as the expected high frequency in Hispanics. Although the numbers are small, homocysteines have been elevated when corrected for age and pregnancy and have correlated with MTHFR homozygosity. Evaluation of both the mother and child for thrombophilia is critical in evaluating etiology, recurrence risks and prevention strategies in NS.